Typology of Nurseries and Adoption’s level of the Technique of Plants Derived Stem Fragment ‘PIF’ for the Production of Plantain Planting Material (Musa spp.) in Côte d’Ivoire - Martin, KOUA Tano Charles; Tchoa, KONE; Yaya, TOURE; Mongomake, KONE (International Journal of Environment, Agriculture and Biotechnology, 2019)
One of the major constraints limiting the development of plantain cultivation is the lack of planting material. In Côte d'Ivoire, to overcome this constraint, the FIRCA (Fond Interprofessionnel pour la Recherche et le Conseil Agricole / Interprofessional Fund for Research and Agricultural Advisory) has organized training workshops on PIF technique (Plants Derived from stem fragment). The objective of this study was to take stock of adoption of the PIF technique for seed production of plantain in Côte d’Ivoire, in order to identify the limits. A survey was carried out in the intervention zones of nurserymen during the periods of October-December 2015 and July-September 2016. The informations collected concern the socio-economic impact of PIF on nurserymen and the level of mastery of the technique by nurserymen. A total of 87 nurserymen were visited. About 75% of the nurserymen are men and 48% are over 46 years old. The purchase price of vivoplants fluctuated between 150 and 250 F. CFA. The number of seedlings sold per nurseryman ranged from 6,000 to 180,000 per year. The survival rate in acclimation was at two months between 40 - 85% and at four months between 35 - 60%. The average number of vivoplants produced per explant ranged from 1.87 to 17.01. 28.73% of the nurserymen used suckers of poor quality and 44.82% of suckers of middle quality. 44.67% of nurserymen have limited control of the reactivation technique. In Côte d’Ivoire, the nurserymen improved the availability of seeds for plantain producers in the form of vivoplants.